2017
DOI: 10.1186/s40200-017-0296-4
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c screening for new onset diabetes following acute coronary syndrome: is it a worthwhile test in clinical practice?

Abstract: BackgroundDiabetes and pre-diabetes are prevalent in acute coronary syndrome (ACS) and relate to adverse outcomes. This study used HbA1c to screen for degrees of glucose intolerance amongst patients without known diabetes presenting with ACS.MethodsOver a 1-year period (June 2014–2015) consecutive patients admitted to a single centre cardiology unit with an initial diagnosis of ACS without prior diabetes diagnosis were electronically referred to our diabetes team. Patients were screened for the presence of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Similar data have been reported by Arnold and his coworkers [10% prevalence of newly diagnosed diabetes in patients with acute myocardial infarction (AMI), previously not known to have diabetes]. [3] Stress hyperglycemia is present in one of four hospitalized patients. In the Study by Gardner et al, stress hyperglycemia was found in 41% of elderly patients with ACS.…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…Similar data have been reported by Arnold and his coworkers [10% prevalence of newly diagnosed diabetes in patients with acute myocardial infarction (AMI), previously not known to have diabetes]. [3] Stress hyperglycemia is present in one of four hospitalized patients. In the Study by Gardner et al, stress hyperglycemia was found in 41% of elderly patients with ACS.…”
Section: Introductionsupporting
confidence: 76%
“…Arnold reported similar data -10% prevalence of T2DM in AMI patients without known diabetes on admission. [3] Maybe the lowest prevalence of NDDM is reported by Chin in an Australian cohort of ACS patients, about 5%. [1] It is evident that there is a significant influence of racial affiliation on the prevalence of diabetes in the general population, and in the cohort of patients with ACS.…”
Section: Graph 5a/5b Predictive Role Of Stress Hyperglycemia In In-hmentioning
confidence: 94%
See 3 more Smart Citations